The effect of Iranian licorice root extract on prostate volume and clinical signs of disease in patients with benign prostatic hyperplasia - Azam Taheri (Shahrekord University of Medical Sciences, 2023)
Background and aims: Benign prostatic hyperplasia (BPH) is the most common benign tumor in men, and its prevalence increases with age. This study aimed to determine the effect of Iranian licorice root extract on prostate volume and clinical signs of BPH disease. Methods: Sixty BPH patients over 40 years old with prostate volume above 30 mL, with symptoms of this disease without drug intervention, were included in the study. First, the Symptom Score AUA (AUASS) questionnaire was completed for all individuals, and then an ultrasound was performed on them. They were then randomly divided into two equal groups. For three months, the intervention group received two capsules of 250 mg of licorice extract daily, and the other group received two placebo capsules. After the study, sonography was performed, and the AUASS questionnaire was completed. Results: 25 and 21 men with BPH in the intervention and placebo groups fully cooperated. At the beginning of the study, prostate volume (P = 0.14) and AUASS were not significantly different between the two groups (P = 0.88). Eventually, prostate volume decreased in the two groups, but the difference between the two groups was not significant (P = 0.33). The AUASS score in the intervention group was significantly lower than the placebo group (P < 0.001). Conclusion: In the present study, the dose of licorice root extract reduced the symptoms of BPH. But further studies with a larger statistical population are needed for this extract to enter the clinic as a drug.